2013
DOI: 10.1007/s00041-013-9292-3
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution from Noisy Data

Abstract: This paper studies the recovery of a superposition of point sources from noisy bandlimited data. In the fewest possible words, we only have information about the spectrum of an object in the lowfrequency band [−f lo , f lo ] and seek to obtain a higher resolution estimate by extrapolating the spectrum up to a frequency f hi > f lo . We show that as long as the sources are separated by 2/f lo , solving a simple convex program produces a stable estimate in the sense that the approximation error between the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
447
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(455 citation statements)
references
References 41 publications
8
447
0
Order By: Relevance
“…Another line of research that relates to this example is that of superresolution (see, e.g., [CFG14,CFG13] and many followup works). These works study the recovery of frequency sparse signals from equispaced samples.…”
Section: Our Main Results and Its Applicationsmentioning
confidence: 99%
“…Another line of research that relates to this example is that of superresolution (see, e.g., [CFG14,CFG13] and many followup works). These works study the recovery of frequency sparse signals from equispaced samples.…”
Section: Our Main Results and Its Applicationsmentioning
confidence: 99%
“…CS is limited by basis mismatch 17 which occurs when the DOAs do not coincide with the look directions of the angular spectrum, and by basis coherence. Solutions to basis mismatch involve for example using atomic norm and solving the dual problem 5,18 that are not addressed here. Grid refinement alleviates basis mismatch for high signal to noise ratio (SNR) at the expense of increased computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…This can be modeled as a CS problem where the sensing matrix is highly coherent and the signal has a spread out support. Recent work on this problem has shown that several optimization based or greedy methods are successful in accurately recovering these types of signals [13,28,29]. Although later we will also consider spread signals, these works are fundamentally different than ours since their goal is exact reconstruction that overcomes the coherent sensing, whereas we are promoting the advantages of coherence sampling when tolerant detection is the goal.…”
Section: Related Workmentioning
confidence: 93%